From Mythical Thinking to Political Thought - Lassan, Eleonora (Respectus Philologicus, 2015)
The article focuses on the Russian epos as well as Russian fairy tales: the images that are frequently there tend to be projected on the contemporary political discourse. The author assumes that the analysis of the folklore stories might allow defining the archetypes, which in a certain manner affect the contemporary political thought in Russia. The author demonstrates the way in which the national cultural archetypes relate to the common cultural ones (Greek myths), on the one hand, and, on the other hand, contain their specific national modification. Thus, the Hero Archetype in Russian epos appears to be nationally marked (its Russianness is particularly stressed) as well as the image of an enemy, filling in the Shadow Archetype. Russian ‘bogatyr’ is traditionally on a state service and remains faithful to his grand duke, notwithstanding the injustice of the latter. The characters of fairy tales wage “preventive wars” in which they become the winners. The contemporary Russian political discourse inherits, to a certain extent, the value as well as the worldview aspects of the Russian epos.
Keywords: political consciousness; archetype; the desire for heroic